Traumatic lumbar hernia with abdominal skin loss (Indian Journal of Case Reports, 2019)
A traumatic lumbar hernia is a rare entity with <100 cases documented in the English literature. Here, we report the case of a 45-year-old man presented with severe abdominal trauma due to two-wheeler road traffic accident. There was a loss of the loin skin, the abdominal muscles severed from the attachment of the iliac crest exposing the cecum and degloving skin extending along the backup to the scapula. He underwent serial debridement to optimize the wound and tensor fascia lata flap skin graft. He had the recurrence of a hernia at 5-month follow-up; for which, he did not want any further surgical interventions. Autologous tissue cover and negative-pressure wound therapy can be considered for cover in a heavily exudating wound.